Estudo da influência da velocidade e dos ciclos de filtração na formação da torta na limpeza de gases em filtros de mangas - Rocha, Sandra Mara Santana (2010)
The permeability and porosity are parameters of great importance for the design of the fabric filter. These parameters affect the pressure drop in the system during operation of filtration as well the strength needed to remove the dust cake. The regeneration of cloth after each filtration significantly alters the properties of filter media. Therefore, the study of the characteristics of formation and removal of the dust cake during the filtration cycles are important to obtain fabric filters more efficient, durable and inexpensive. In this context, this study aimed to investigate the influence of filtration cycles on the structure of dust cake formed from different velocities of filtration. To this end, experiments were performed with filtration velocity of 5, 10 and 15 cm:s1, and 100 cycles of filtration with mean surface velocity of 5 and 15 cm:s1, with pressure drop maximum of 2300 and 9000 Pa, respectively. The study of the influence of filtration velocity and number of cycles in the fluid dynamics of gas were performed using a technique of CFD (Computational Fluid Dynamics). To obtain such information, tests were performed on filtration equipment belonging to the Laboratory of Environmental Control, Department of Chemical Engineering at Federal University of São Carlos, which consisted of a circular filter with filter-free area of 249 cm2 with a mass flow rate and humidity on the air in a controlled system acquisition system data. The filter media used was a polyester felt (weight 534 g:cm2), a polypropylene (weight 600 g:cm2) and cotton (weight 735 g:cm2). The powder material used was the phosphate concentrate (p = 2.79 g:cm3). Micrographs of cloth were obtained by SEM (Scanning Electron Microscope), which they were analyzed in a specific image program and with this micrographs were possible to obtain the values of average porosity. Based on these results, it could be concluded that the clogging of the filter medium was dependent on the rate of filtration, being the time of its formation less for higher velocity. These velocities were also responsible for the accumulation of greater numbers of particles in deeper regions of the filter medium. The results with velocity of 15 cm:s1 show a high mass collected on filter, but this has not released much mass during the cleaning operation. This velocity also showed the greatest loss, since the particles remaining from cleaning clogged pores of the fabric and tended to increase the resistance of the flux of air. The porosity values measured directly were around 15% lower than the values estimated by correlation of Ergun. In relation of the number of cycles, from cycle 70 to the velocity of 5 and 15 cm:s1, the mass removed was almost equal, ie the rate of filtration no longer influenced the mass removed. On the other hand, the pressure drop had a variation in the number of cycles. The fluid dynamic study of the gas was done through simulations using the technique of CFD, which found that the filtration rate has great influence on the fluid dynamics of gas that, the number of cycles. With reference to the simulations in cotton fabric and felt of polypropylene, the latter was more favorable for the filtration of gases, compared to cotton, both experimentally and via simulations in CFD.